2012
DOI: 10.1016/j.jhazmat.2012.09.064
|View full text |Cite
|
Sign up to set email alerts
|

Using slow-release permanganate candles to remediate PAH-contaminated water

Abstract: Surface waters impacted by urban runoff in metropolitan areas are becoming increasingly contaminated with polycyclic aromatic hydrocarbons (PAHs). Slow-release oxidant candles (paraffin-KMnO(4)) are a relatively new technology being used to treat contaminated groundwater and could potentially be used to treat urban runoff. Given that these candles only release permanganate when submerged, the ephemeral nature of runoff events would influence when the permanganate is released for treating PAHs. Our objective wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Given that adsorption tests confirmed that neither diphenaldehyde or the ozone-treated benzo(a)pyrene products were adsorbed by the glass beads or glass beads coated with microorganisms ( Figure SM-7), the losses in 14 C recovered confirm that biological mineralization could be achieved in a flow-through system and mineralization rates improved with repeated cycles. Collectively, the results reported in this study, combined with previous chemical-biological approaches (Zeng et al, 1999;Zenaitis et al, 2002;Yerushalmi et al, 2006;Rauscher et al, 2012), support combining ozone with biological treatments for treating PAH-contaminated water. …”
Section: Biodegradation and Mineralization Of Diphenaldehyde And O 3 supporting
confidence: 74%
See 3 more Smart Citations
“…Given that adsorption tests confirmed that neither diphenaldehyde or the ozone-treated benzo(a)pyrene products were adsorbed by the glass beads or glass beads coated with microorganisms ( Figure SM-7), the losses in 14 C recovered confirm that biological mineralization could be achieved in a flow-through system and mineralization rates improved with repeated cycles. Collectively, the results reported in this study, combined with previous chemical-biological approaches (Zeng et al, 1999;Zenaitis et al, 2002;Yerushalmi et al, 2006;Rauscher et al, 2012), support combining ozone with biological treatments for treating PAH-contaminated water. …”
Section: Biodegradation and Mineralization Of Diphenaldehyde And O 3 supporting
confidence: 74%
“…Many of these products would be more soluble and thus more available for natural biotic mineralization than the original parent structure, which was evident from our mineralization results ( Figure 6B). Nam and Kukor (2000); Rauscher et al (2012) also found that oxidative treatment of PAHs resulted in more biological products.…”
Section: Biodegradation In Soil Microcosmsmentioning
confidence: 98%
See 2 more Smart Citations
“…Chemical analysis of PAHs is of great environmental and toxicological importance as many PAHs have been identified as potent mammary carcinogens in experimental bioassays (Elbayoumy, 1992). Exposures to PAHs have been linked to increased cancer risks in epidemiological studies (Mastrangelo et Due to their hydrophobicity, PAHs are inclined to adsorb to and accumulate with particles such as dust, sediment and debris, Atmospheric PAHs may undergo photolytic and chemical (ozone) transformations or be deposited back to land (Rauscher et al, 2012;Xie and Haleegoah, 2016). A primary route of human exposure to PAHs is the ingestion of contaminated water, which is one of the indispensable materials in daily human life.…”
Section: Introductionmentioning
confidence: 99%